(untitled) (AmeriQuests, 2014)
Pre-removal detention is usually considered an administrative measure aimed at the facilitation of the removal of irregular migrants by preventing them from absconding during removal proceedings. The administrative nature of immigration detention implies that persons subject to this measure do not have access to the fair trial guarantees that criminal detainees are entitled to. However, the assessment of pre-removal detention under European Union and Swiss legislation demonstrates the penal nature of such detention despite its formal administrative classification. The penal nature of immigration detention is most easily revealed by the explicit deterrent—if not punitive—function it is supposed to fulfill in order to force foreigners to cooperate in their own removal procedure. Moreover, this penal nature may also be deducted from the more implicit purpose of immigration detention to punish irregular migrants and asylum seekers for criminal offences. The discrepancy between the administrative label of immigration detention and its punitive nature should be remedied. Arguably, the use of pre-removal detention should be limited to a truly administrative purpose, i.e. for very short periods of time allowing the state to prevent concrete risks of absconding once removal is about to be enforced. Alternatively, if the existing legal framework fails to prevent the use of immigration detention according to disciplinary or punitive functions, immigration detainees should be afforded guarantees comparable to those applied in criminal proceedings.